Rhein inhibits the growth of Propionibacterium acnes by blocking NADH dehydrogenase-2 activity. Issue 5 (4th May 2020) - Nguyen, Anh Thu; Kim, Ki-young
Abstract : Introduction. Rhein (4, 5-dihydroxyanthraquinone-2-carboxylic acid) has various properties, including anti-inflammatory, antioxidant and anticancer activities. However, the mechanism underlying the role of rhein in antimicrobial activity remains largely unknown. Aim. This study aims to identify potential natural compounds of rhein that are capable of inhibiting Cutibacterium acnes and elucidate the effects of rhein on NADH dehydrogenase-2 activity in C. acnes . Methodology. The anti -C. acnes activity of compounds was analysed using minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), the paper disc diffusion test and the checkerboard dilution test. To check whether rhein was inhibitory, putative type II NADH dehydrogenase (NDH-2) of C. acnes was analysed, cloned and expressed in Escherichia coli, and then NDH-2 purification was assessed with Ni-NTA before rhein inhibition of NADH dehydrogenase-2 activity was checked with ferricyanide [K3 Fe(CN)6 ] as a substrate. Results. The results showed that the MIC of rhein against C. acnes was 6.25 µg ml −1, while the MBC was 12.5 µg ml −1, and there was a 38 mm inhibition zone in the paper disc diffusion test. Rhein showed an additive two- to fourfold reduction of the MIC value with four antibiotics on the checkerboard dilution test. The purified NADH dehydrogenase gene product showed a size of approximately 51 kDa and had a V max of 23 µmol and a K m of 280 µm. The inhibitory effect of rhein against NADH dehydrogenase-2 activity was non-competitive with ferricyanide [K3 Fe(CN)6 ] with a K i value of 3.5–4.5 µm. Conclusion. This study provided evidence of the inhibitory effects of rhein on the growth of C. acnes by blocking of NADH dehydrogenase-2 activity. This mechanism of inhibitory activity in the reduction of ROS formation and ATP productivity should be further tested in C. acnes and the question of whether rhein inhibits the natural growth of C. acnes should be investigated.